Direct Adhesive Pin-Retained Restorations for Severely Worn Dentition Treatment: A 1.5-Year Follow-Up Report - ANDRADE, Camila Lima de (2015)
Excessive occlusal surface wear can result in occlusal disharmony, functional and esthetic impairment. As a therapeutic approach, conventional single crowns have been proposed, but this kind of treatment is complex, highly invasive and expensive. This case report describes the clinical outcomes of an alternative minimally invasive treatment based on direct adhesive-pin retained restorations. A 64-year-old woman with severely worn dentition, eating problems related to missing teeth and generalized tooth hypersensitivity was referred for treatment. Proper treatment planning based on the diagnostic wax-up simulation was used to guide the reconstruction of maxillary anterior teeth with direct composite resin over self-threading dentin pins. As the mandibular remaining teeth were extremely worn, a tooth-supported overdenture was installed. A stabilization splint was also used to protect the restorations. This treatment was a less expensive alternative to full-mouth rehabilitation with positive esthetic and functional outcomes after 1.5 years of follow-up.